2017
DOI: 10.5194/hess-2017-512
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Frequently used drought indices reflect different drought conditions on global scale

Abstract: Abstract. Drought is an abnormal and prolonged deficit in available water. Possible drought impacts are crop losses, famine, fatalities, power blackouts and degraded ecosystems. These severe socio-economic and environmental impacts show the need to carefully monitor drought conditions using a suitable index. Our objective is to provide an intercomparison of frequently used physical drought indices to show to which degree they are interchangeable for monitoring drought in precipitation, soil moisture, groundwat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 23 publications
2
28
0
Order By: Relevance
“…Drought events were determined using the variable threshold method (Yevjevich, 1967;Hisdal et al, 2004). Drought starts when the groundwater or runoff data fall below a certain threshold value and ends when it is equal or rises above the threshold (Eq.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drought events were determined using the variable threshold method (Yevjevich, 1967;Hisdal et al, 2004). Drought starts when the groundwater or runoff data fall below a certain threshold value and ends when it is equal or rises above the threshold (Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Minor meteorological drought may not develop into a hydrological drought, but a series of meteorological droughts can evolve into one long hydrological drought. Specific hydrological drought studies also indicate that hydrological drought diverges from meteorological drought due to its complex phenomenon and different catchment characteristics (Peters et al, 2003;Vidal et al, 2010;Van Dijk et al, 2013;Van Loon and Van Lanen, 2012;Van Lanen et al, 2013;Wanders et al, 2017). Moreover, drought impacts, such as water supply, water-borne transport, and hydropower energy production are more closely linked with hydrological drought rather than with meteorological ones.…”
Section: Introductionmentioning
confidence: 99%
“…Their slow onset and slow recovery, the different drought categories (Figure ) and impacted sectors (Table ) make droughts very difficult to define quantitatively, giving rise to a multitude of indices. Reviews of drought indices can be found in Heim Jr., Keyantash and Dracup, Hisdal et al, Niemeyer et al, Mishra and Singh, Wanders et al, Dai, Sheffield and Wood, Seneviratne et al, and Tsakiris et al The choice of index and its implementation are important as they can result in different conclusions, especially in the light of trends and global change . However, there seems to be scientific consensus that there is no ‘best’ hydrological drought index and that a quest for the ‘best’ index is useless .…”
Section: Hydrological Drought Quantificationmentioning
confidence: 99%
“…Additionally, the length of a precipitation record and the fitted probability distribution have significant impact on the SPI values . Finding the most suitable distribution can be a challenge, especially in dry climates, which limits the use of SPI on a global scale.…”
Section: Hydrological Drought Quantificationmentioning
confidence: 99%
“…In terms of drought, a hydrological drought is defined as a negative anomaly in surface and subsurface water levels (Van Loon, 2015;Wanders et al, 2017). These negative anomalies on the surface, related to a level of water demand can cause water systems to collapse and trigger strong socioeconomic impacts or the so-called socioeconomic drought (Mehran et al, 2015).…”
Section: Introductionmentioning
confidence: 99%